Bioreduction of a Drug Intermediate in Presence of Hexane and Surfactants - Brahmani Priyadarshini, S.R.; Mugeraya, Gopal; Sandhyavali, M.S. (Asian Journal of Chemistry, 2010)
Enhancing the dispersion and dissolution of substrate particles in substrate/water suspension is a feasible way to improve enzyme substrate contact. The aim of the present study is to investigate the effects of organic solvents like hexane and surfactants like sodium lauryl sulphate (SLS) and cetyltrimethyl ammonium bromide (CTAB) on bioreduction of 3-[5-[(4-flurophenyl)-1,5, di-oxopentol]-yl]-4-(s)-phenyloxazolidin-2-one using Sacchromyces cerevisiae as biocatalyst. Effect of variations in the ratio of hexane to water and the concentration of an anionic and cationic surfactants, were studied to see their effect on the bioreduction of the above mentioned ketone. As the substrate is hydrophobic, the bioreduction was tried in a biphasic system using solvent like hexane. The overall yield of the alcohol decreased significantly when the reaction was carried out in presence of hexane as compared to aqueous medium. The yield of alcohol increased when the ratio of hexane to water was 2:1, but decreased significantly with further increase in hexane concentration. The use of surfactants has been reported extensively in microbial biotransformation reactions. Hence the effect of both anionic (sodium lauryl sulphate) and cationic (cetyltrimethyl ammonium bromide) surfactants on the above said bioreduction was considered for the study. The results showed that cetyltrimethyl ammonium bromide has insignificant effect in bringing about ketone reduction while sodium lauryl sulphate exhibited three fold increase in the yield.